2019
DOI: 10.21031/epod.419625
|View full text |Cite
|
Sign up to set email alerts
|

Tek Denekli Deneysel Çalışmalarda Etki Büyüklüğü Hesaplaması: Regresyona Dayalı Olmayan Yöntemlerin İncelenmesi

Abstract: Tek denekli deneysel çalışmalarda meta-analiz yöntemlerine grup desenli çalışmalarda olduğu kadar yer verilmediği gözlenmektedir. Son yıllarda alanyazındaki bu eksikliği gidermek amacıyla tek denekli deneysel çalışmalarda etki büyüklüğü olarak kullanılabilecek regresyona dayalı olan ve regresyona dayalı olmayan indeksler geliştirilmiştir. Regresyona dayalı olan indekslerin çoğu tek denekli deneysel araştırma verilerindeki zamansal bağımlılıktan etkilendiği için bu indekslerden daha az etkilenen ve alanyazında … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Recently, however, it has become more common for researchers to use methods in addition to visual data analysis to report intervention effectiveness to support conclusions from single-subject designs (Olive & Smith, 2005). Both regression and nonregression effect size calculations (e.g., standard mean difference, percentage reduction measure, per cent reduction, percentage exceeding the median) have therefore been developed and reviewed (e.g., Olive & Franco, 2008;Olive & Smith, 2005;Şen & Şen, 2019).…”
Section: Analysis Of Single-subject Design Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, it has become more common for researchers to use methods in addition to visual data analysis to report intervention effectiveness to support conclusions from single-subject designs (Olive & Smith, 2005). Both regression and nonregression effect size calculations (e.g., standard mean difference, percentage reduction measure, per cent reduction, percentage exceeding the median) have therefore been developed and reviewed (e.g., Olive & Franco, 2008;Olive & Smith, 2005;Şen & Şen, 2019).…”
Section: Analysis Of Single-subject Design Datamentioning
confidence: 99%
“…Through such reviews it has been confirmed that nonregression methods are successful in identifying intervention effectiveness within single-subject experimental data (Olive & Smith, 2005). However, regression-based calculation methods have been shown to be affected by the serial dependency of single-subject design data and should be avoided (Olive & Smith, 2005;Şen & Şen, 2019). Therefore, it has been recommended that a nonregression effect size calculation be used in combination with visual data analysis to provide statistical evidence of intervention effectiveness (Olive & Franco, 2008).…”
Section: Analysis Of Single-subject Design Datamentioning
confidence: 99%
“…We then computed the percentage of data exceeding the median trend of the baseline (PEM-T; White & Haring, 1980;Wolery et al, 2010), which is an effect size index used in single-subject research. PEM-T is conceptualized as the % of datapoints in the therapy phase that are above the median slope (or split middle line) plotted based on pretherapy data and extended to the therapy phase (Manolov & Moeyaert, 2016;Parker et al, 2011;Rakap, 2015;Şen & Şen, 2019). Importantly, PEM-T is a non-parametric nonoverlap method that controls for baseline trends in a therapeutic direction as part of nonoverlap (i.e., positive trend during baseline in case an increase of behavior is expected with treatment; Parker et al, 2011;Rakap, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Pendekatan lain yang dapat digunakan untuk melakukan analisis data penelitian subjek tunggal dapat menggunakan persentase data yang tidak tumpang tindih (percentage of nonoverlapping data/PND) untuk setiap subjek penelitian (Manolov & Solanas, 2009;Parker et al, 2007;Scruggs & Mastropieri, 1998, 2001. Pada teknik analisis data ini dilakukan dengan cara (1) menentukan nilai baseline maksimum pada grafik, (2) menarik garis horizontal dari nilai maksimum yang ditentukan ini ke kanan (tingkat intervensi), (3) menentukan nilai tingkat intervensi di atas garis horizontal ini, (4) membagi jumlah titik data yang diperoleh pada langkah ketiga dengan jumlah total titik data pada tingkat intervensi, dan (5) nilai yang diperoleh pada langkah keempat dikalikan dengan 100 untuk menghitung nilai PND (Sşen & Sşen, 2019). Asumsi yang digunakan pada teknik analisi data ini adalah jika PND>90% maka intervensi yang diberikan kepada subjek sangat efektif, jika diperoleh PND antara 71% hingga 90% maka intervensi dapat dinyatakan efektif, jika diperoleh PND antara 50% hingga 70% maka intervensi kategori sedang, jika PND kurang dari 50% maka tidak efektif (Scruggs et al, 1986;Strain et al, 1992).…”
Section: Teknik Analisis Data Pada Single Subject Researchunclassified